Presence of Salmonella enterica from retail chicken meats: preliminary findings - Tugba Aydin; Elif Bozcal (Journal of Global Antimicrobial Resistance)
AIM: The aim of this study was the isolation and identification of Salmonella serovars from retail chicken meats, determination of their serovars, and mobile colistin resistance genes. BACKGROUND: Salmonella spp. is a member of the Enterobacteriaceae family that threatens public health. It can cause infection and epidemics in humans through the consumption of contaminated foods including meat and dairy products.Colistin is a last resort antibiotic in the fight against infection in the clinic. Zoonotic foodborne pathogens such as non-typhoidal serotypes of Salmonella enterica, may cause colistin resistance to spread throughout the food chain. METHODS: 80 retail chicken meats were collected from different districts of Istanbul between April and May 2024. Phenotypic diagnostic tests were performed and Salmonella genus-specific invA and spvC virulence genes were amplified via PCR. O and H serotyping tests were performed with the slide agglutination technique. Later on, colistin resistance genes including mcr-1, mcr-2, mcr-3, mcr-4, and mcr-5 were investigated in strains identified as Salmonella spp. RESULTS: out of 80 samples, 15 (18.75%) Salmonella spp. strains were identified by phenotypic and genotypic methods. As a result of serotyping, Salmonella spp. strains were detected as Non-typhoidal Salmonella enterica. Additionally, mcr-2 and mcr-3 colistin resistance genes were detected in 8 S. enterica subspecies. CONCLUSIONS: S. enterica serovars carrying colistin resistance genes in foods may pose a threat to human health. Multidrug resistance profiles in the poultry industry and the increasing prevalence of virulent Salmonella serovars in farm animals and humans may present alarming features in terms of food safety.